Substantiation of the temperature regime of the differential pump of electromagnetic action (Academic journal Industrial Machine Building Civil Engineering, 2021)
The article discusses the temperature of the working body caused by Foucault currents circulating inside of the working body of a differential pump of electromagnetic action. The article begins with a theory describing the nature of the Foucault current and the causes of the plunger heating. Then there is a characteristic of the differential pump of electromagnetic action. The following is a description of the structures of the working bodies of the differential pump of electromagnetic action. The estimated data of the working body are entered in the table. These tables are taken into account when plotting. The theory substantiates the conditions of heating of the working body, the existence of eddy currents, and also the influence of the temperature of the actuator on the operation of the differential pump. The description shows what role the plunger plays in the operation of the differential pump. The article described in detail the interaction of the working body and the solenoid of the differential pump.
Keywords: differential pump; finishing mixture; plunger; Foucault current